Peran Komitmen Organisasional Dalam Memediasi Pengaruh Self Efficacy Terhadap Organizational Citizenship Behavior: Studi di PT. BPR Gianyar Parthasedana di Gianyar - Handayani, Ni Made Dwi; Wulandari, Ni Luh Adisti Abiyoga (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2022)
Human resources are important in organizations because they act as determinants, planners, implementers and analyzers of all activities to achieve the expected goals. The purpose of this study was to determine the effect of self efficacy and organizational commitment on organizational citizenship behavior either directly or indirectly at PT. BPR Gianyar Parthasedana in Gianyar. The samples taken were 44 respondents. Data was collected by observation, interviews, questionnaires and literature study. The analysis technique used is validity test, reliability test, path analysis and Sobel test. The results of the analysis show that (1) self efficacy has a positive and significant effect on organizational commitment (2) organizational commitment has a positive and significant effect on organizational citizenship behavior (3) self efficacy has a positive and significant effect on organizational citizenship behavior (4) organizational commitment has a positive and significant effect in mediating the effect of self efficacy on organizational citizenship behavior. Suggestions to the PT. BPR Gianyar Parthasedana should always pay attention to self efficacy and organizational commitment to support employee organizational citizenship behavior.